The Presidential Elections of 2018 in Georgia: Anatomy of Competitive Authoritarianism - Zedginidze, Natia; Orjonikidze, Tamar (Politics / პოლიტიკა; 2019: მეორე ნომერი, 2019)
There is discussed the results of Presidential elections of 2018 year in Georgia on the bases of Anatomy of Competitive Authoritarianism. In particular, there are shown two important aspects of the sense of competitive authoritarianism: Inequality of government and opposition in terms of attracting election finance and an unsuccessful attempt to develop a document reflecting the ethical principles of behavior of election subjects during the election campaign. The article is prepared on the basis of electronic and printed media materials regarding the election campaign finances, as well as interviews with people involved in development of the ethical principles presidential candidates behavior.
Keywords: Keywords: Georgia, Competitive Authoritarianism, Elections, Democratization.